Sistem Perangkingan Saham Perusahaan Index LQ45 Terbaik Menggunakan Metode Simple Additive Wighting (SAW) - Nadhif Nasrudin; Harunur Rosyid (SABER : Jurnal Teknik Informatika, Sains dan Ilmu Komunikasi, 2024)
Information technology is developing rapidly and widely in various fields today and provides convenience in all activities. One of them is in buying and selling company shares. In the process of buying shares, there are still many investors who buy a stock without analyzing it. In a stock transaction, the need to determine the quality of the shares to be purchased is very important because it must be able to analyze the shares in accordance with the objectives and targets that are the guidelines for buying shares. The LQ45 Index is a combined calculation of 45 company shares that will be assessed and selected through several criteria including stocks that have high liquidity, are included in the 45 stocks that have the largest transactions, and have been listed for at least 3 months on the Indonesia Stock Exchange.